Beckett’s Paradox: Exploring the Abyss of Human Existence - Nasir, Muhammad Saeed; Umair, Muhammad; Khudai, Unaiza; Rashid, Abdul (Pakistan Journal of Humanities and Social Sciences, 2023)
This paper examines how do themes of suffering, despair, and insignificance find in Samuel Beckett’s works. Employing a perspective of reader response theory, a thorough analysis of Beckett’s prominent works traces the nihilistic view of human existence within Beckett’s narrative.It reveals that Beckett’s well-crafted characters are trapped in a futile world and it hardly allows them to be free.It concludes with the assertion that Beckett’s works as a poignant reflection on the human condition, depicting struggles and disillusionment by individuals in a world devoid of inherent purpose. As it also deals with Beckett’s lesser-known works, it expands the horizon of Beckett scholarship by enhancing our understanding of Beckett’s profound contributions to the literary canon.